1996
DOI: 10.1002/(sici)1097-0142(19960215)77:4<805::aid-cncr29>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic neuroblastoma in children older than one year: Prognostic significance of the initial metaiodobenzylguanidine scan and proposal for a scoring system

Abstract: The initial mIBG scan is of prognostic significance to predict response to chemotherapy for metastatic neuroblastoma in children older than 1 year of age. A prospective study comparing this initial mIBG score with other recently established prognostic factors is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(29 citation statements)
references
References 25 publications
0
28
0
1
Order By: Relevance
“…It is used in the diagnosis, staging, and reassessment of patients with neuroblastoma, and has been shown to be highly sensitive and specific in this condition. 4 Meanwhile, MRI is extremely sensitive in detecting abnormalities of bone marrow. Bone marrow involvement (with or without bony involvement) is seen as areas of decreased signal intensity on T 1 -weighted images because of the replacement of the fat tissue normally seen with high signal intensity by tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…It is used in the diagnosis, staging, and reassessment of patients with neuroblastoma, and has been shown to be highly sensitive and specific in this condition. 4 Meanwhile, MRI is extremely sensitive in detecting abnormalities of bone marrow. Bone marrow involvement (with or without bony involvement) is seen as areas of decreased signal intensity on T 1 -weighted images because of the replacement of the fat tissue normally seen with high signal intensity by tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…To evaluate the prognostic effect of tumour burden at diagnosis and to be able to quantify response and define a partial response (50% reduction of all disease sites) by mIBG scan, semiquantitative scoring systems have been developed (Ady et al, 1995;Suc et al, 1996;Perel et al, 1999;Frappaz et al, 2000;Matthay et al, 2003b;Katzenstein et al, 2004;Messina et al, 2006;Lewington et al, 2009). This improves the concordance between readers, and enables one to differentiate a simple improvement with the disappearance of a lesion, or decreased intensity of lesions that can be subjective, from a significant response that would qualify as PR.…”
Section: Semi-quantitative Mibg Scoringmentioning
confidence: 99%
“…Previous studies have indicated that a positive mIBG scan after induction chemotherapy or just before myeloablative therapy may be a prognostic marker for a high likelihood of relapse (Ladenstein et al, 1998;Perel et al, 1999;Schmidt et al, 2008). Several publications have reported the use of semi-quantitative scoring systems to increase the precision and inter-observer reliability of this test, with success in correlating the results of mIBG scans with early response and event-free survival in some, but not all, reports (Ady et al, 1995;Suc et al, 1996;Frappaz et al, 2000;Hero et al, 2001;Matthay et al, 2003b;Katzenstein et al, 2004). As treatment of stage 4 neuroblastoma continues to be a challenge, with a high rate of relapse in bone and bone marrow, it is essential to have a quantitative and reliable measure of response in bone metastases to test the activity of new therapies for this disease (Messina et al, 2006).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In order to evaluate the prognostic effects and quantify efficacy of therapy, a number of semi-quantitative scores have emerged [14][15][16][17][18][19] and have been shown to be essential for the evaluation and quantification of response to the treatment [12,20,21].…”
Section: Introductionmentioning
confidence: 99%